2018
DOI: 10.1021/acs.bioconjchem.8b00459
|View full text |Cite
|
Sign up to set email alerts
|

Tracing Hematopoietic Progenitor Cell Neutrophilic Differentiation via Raman Spectroscopy

Abstract: A major challenge to experimental studies and therapeutic uses of hematopoietic stem cells (HSC) is the limited options for analytical tools that can reliably resolve functional differences in heterogeneous HSC subpopulations at the single cell level. Currently available methods require the use of external labels and/or separate clonogenic and transplantation assays to identify bona fide stem cells, necessitating the harvest of bulk cell populations and long incubation times that obscure how individual HSCs dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 58 publications
0
19
0
Order By: Relevance
“…Raman microspectroscopy is a label-free technique which has been applied to study phenotypes of single cells ( 13 15 ). It is a nondestructive vibrational spectroscopy based on inelastic scattering of light, reflecting the intrinsic biochemical profiles of cells ( 16 ).…”
mentioning
confidence: 99%
“…Raman microspectroscopy is a label-free technique which has been applied to study phenotypes of single cells ( 13 15 ). It is a nondestructive vibrational spectroscopy based on inelastic scattering of light, reflecting the intrinsic biochemical profiles of cells ( 16 ).…”
mentioning
confidence: 99%
“…The pinhole size was set to 500 m, the slit size to 100 m, and the grating to 300 groves per mm. Raman scattering was acquired for the fingerprint region from 600 to 1750 cm -1 for 20 s per cell [12,15,24]. Spectra were aligned to the peak of phenylalanine at 1004 cm -1 , which is used as the reference peak because it is always present on the cell spectra.…”
Section: Acquisition Of Raman Spectramentioning
confidence: 99%
“…Our lab was also able to distinguish different Chinese Hamster Ovary (CHO) host and production cell lines by Raman microspectroscopy (Prats Mateu et al 2017). In chondrocytes (Pudlas et al 2013), hematopoetic stem cells (Ilin et al 2015), and hematopoetic progenitor cells (Choi et al 2018), it has been shown that Raman microspectroscopy is capable of monitoring the dynamic process of cell differentiation. Also, different cellular states, such as apoptosis and necrosis, were successfully distinguished (Brauchle et al 2014b), and cell progression through mitosis was followed by Raman microspectroscopy (Matthäus et al 2006).…”
Section: Raman Microspectroscopy Distinguishes Cellular States In a Lmentioning
confidence: 99%